El problema de la cultura en Levinas - Navarrete Jacobo, Raúl (Universidad Michoacana de San Nicolás de Hidalgo., 2009)
Beyond the geographical component that locates like in a pleat to Lithuania with regarding Russia and Western Europe, the culturally open Judaism arisen to principles of the XX century can be explained starting from a historical special gestation. From the XVIII and XIX centuries a movement of Jewish illustration also denominated it was "of the lights" or Haskalá, he/she extended through eminent rabbis in those Jewish communities of oriental Europe. Their principle "Knows a judío in your house and a man outside of her" 1 gave entrance so that a millennial tradition reconsidered the one external world as necessary in their vital consolidation. The Jew of Haskalá to look after their tradition, but that care should not prevent him/her to be well educated and rational for to dialogue in all moment through her. The Jewish illustration or Haskalá maintained this way in a cultural attentive opening to the Hebrew community that he/she inhabited the Lithuanian country. A cultured one, Rabbi Eliahu, gaón of Vilna (1720 -1797) he/she attempted to their way to cultivate this Jewish Haskalá. In their fight against the tsaddikim or miraculous" "rabbis, it arrived to believe that the Jews could not be faithful to the dialectical tradition of the Judaism, tradition gathered in Talmud, following such characters. The study of the books and its discussion should overcome this merely magic and contemplative focus that had been encouraged from their followers, the jasidim. Their more outstanding student, Rabbi Jaim of Volozin (1959 -1821) he/she would even have dedicated their life to continue Haskalá of its teacher. He/she was founded in 1802 the first academy or Lithuanian Yeshiva. Their orientation was firmly delineated: to recover a dialectical religiosity.

Más allá del componente geográfico, que sitúa como en un pliegue a Lituania con respecto a Rusia y Europa occidental, el judaísmo culturalmente abierto surgido a principios del siglo XX puede explicarse a partir de una especial gestación histórica. Desde los siglos XVIII y XIX un movimiento de ilustración judía también denominado Era de las luces o Haskalá, se extendió a través de eminentes rabinos en las comunidades judías de la Europa oriental. Su principio Sé un judío en tu casa y un hombre fuera de ella 1 dio entrada para que una tradición milenaria reconsiderara al mundo exterior como necesario en su consolidación vital. El judío de la Haskalá debía velar por su tradición, pero ese cuidado no debía impedirle ser instruido y racional para dialogar en todo momento a través de ella. La ilustración judía o Haskalá mantenía así en una atenta apertura cultural a la comunidad hebrea que habitaba el país lituano. Un ilustrado, Rabí Eliahu, gaón de Vilna (1720-1797) intentó a su manera cultivar esta Haskalá judía. En su lucha contra los tsadikim o rabinos milagrosos, llegó a creer que los judíos no podían ser fieles a la tradición dialéctica del judaísmo, tradición reunida en el Talmud, siguiendo a tales personajes. El estudio de los libros y su discusión debía superar este enfoque meramente mágico y contemplativo que había sido alentado desde sus seguidores, los jasidim. Su alumno más destacado, Rabí Jaim de Volozin (1959-1821) habría incluso dedicado su vida a continuar la Haskalá de su maestro. Fundó en 1802 la primera academia o Yeshiva lituana. Su orientación estaba firmemente delineada: recuperar una religiosidad dialéctica.
Instituto de Investigaciones Filosóficas. Facultad de Filosofía. Programa Institucional de Maestría en Filosofía de la Cultura
Keywords: info:eu-repo/classification/cti/4; Lituania; Haskalá; Estrasburgo; IIF-M-2009-0018; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/11